The Organizational Climate and its Impact on the Innovative Behavior of Auditors - Abbas, Ali; Mousa, Hazem; Ali, Hussam (The Arab Journal of Administration, 2021)
The research aims to know the type of organizational climate prevailing in the organization under study and the type of relationship with the innovative behavior of auditors, and to know the extent to which the auditor was affected by the type of climate in the organization, whether positive or negative and to address the weaknesses that appear. A sample consisting of (105) was selected from the accountants and auditors working for the General Company for the Automotive Industry in Baghdad, all of the accountants and auditors, was taken. Data were collected by distributing the questionnaire, and the main hypothesis was fulfilled and a positive relationship effect of organizational climate on the innovative behavior of auditors was established. Several sub-hypotheses were fulfilled, and a set of important recommendations was made to address the vulnerability in some areas where there was a weak effect relationship on the dimensional level of the independent variable with the dependent variable. The previous studies were used in setting the dimensions of the dependent and independent variables. And that each organization has its organizational climate and even at the level of departments within the same organization, so leaders must be fully aware of all environmental changes that may cause change or damage to the organizational climate, work to find remedies for problems through the development of new solutions and not dependence On previous solutions to new problems. The organization must work to increase the moral and material incentives for workers who have innovative behavior.